Hubungan Antara Intensitas Kebisingan Aktivitas Penerbangan di Bandara Adi Sucipto dengan Nilai Ambang Pendengaran pada Anak - Mieng Nova Sutopo, B.U. Djoko Rianto, Nawi Ng (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: With its increasing status as international airport, the intensifying flight activities at Adi Sucipto Airport in Yogyakarta City poses a public health problem to its surrounding community. A preliminary study conducted by the Directorate of Environmental Sanitation, Directorate General of Disease Control and Environmental Sanitation of the Ministry of Health and Environmental Health Engineering Council of Yogyakarta, at an elementary school located in the Noise Area Limit II showed the noise level of 71.4 dBA, and subjective complaints from respondents included difficulty to sleep (46.5%), frequent waking up at night (45.1%), and lack of sleep (42.2%). Forty three out of 70 students studied experienced decrease of hearing capability.Objective: The objective of the study was to identify relationship between noise intensity and level of hearing limit among elementary school students at Noise Area Limit II of Adi Sutjipto Airport, Yogyakarta. The study was conducted at two elementary schools within the Noise Area Limit II, one situated closely to the airport and the other one at the outer ring of the area.Method: The study was analytical with cross sectional study design.Result: The airplane noise intensity, either measured at school or subject residence, showed no significant differences between Kali Ajir Lor and Perumnas Condong Catur Elementary School. The duration of exposure is amongst the important factor which might explain the difference of hearing impairment observed in this study.Conclusion: Length of exposure to noise intensity is statistically significant to the level of hearing impairment among students studied.Keywords: noise area limit, noise intensity, hearing disorder